Respuesta :

Answer:

f(g(x)) = g(f(x)) = x

Step-by-step explanation:

To prove two functions, say f(x) and g(x) are inverses to each other, we take the composition of the two functions: f(g(x)) and g(f(x)) and prove that:

                       f(g(x)) = g(f(x)) = x, x is the identity function

Now, given:

[tex]$ f(x) = \frac{\sqrt[3]{x + 4}}{7} $[/tex]         and          [tex]$ g(x) = (7x)^3 - 4 $[/tex]

Calculate: f(g(x)):

[tex]$ f(g(x)) = f((7x)^3 - 4) $[/tex]

It means to substitute [tex]$ (7x)^3 - 4$[/tex] in place of x.

Therefore, we get:

[tex]$ f(g(x)) = \bigg \{ \frac{ \sqrt[3]{(7x)^3 - 4 + 4}}{7} \bigg \} $[/tex]

[tex]$ f(g(x)) = \bigg \{ \frac{ \sqrt[3]{(7x)^3}}{7} \bigg \} $[/tex]

           [tex]$ = \frac{(7x)}{7} $[/tex]

           = x, the identity function.

Now compute g(f(x))

[tex]$ g(x) = (7x)^3 - 4 $ \therefore g(x) = 343x^3 - 4 $[/tex]          

Now, [tex]$ g(f(x)) = 343 \bigg \{ \bigg ( \frac{\sqrt[3]{x + 4}}{7} \bigg ) ^3 \bigg \} - 4[/tex]

                      [tex]$ = 7^3 \frac{x + 4}{7^3} - 4 $[/tex]

                      [tex]$ = (x + 4) - 4 $[/tex]

                      = x

We have proved f(g(x)) = g(f(x)) = x. Hence, they are inverses of each other.

ACCESS MORE